Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1)\(2x^2+9y^2-6xy-6x-12y+2004\)
\(=x^2+x^2-6xy+9y^2-6x-12y+2004\)
\(=x^2+\left(x-3y\right)^2-10x+4x-12y+2004\)
\(=\left(x-3y\right)^2+4\left(x-3y\right)+x^2-10x+2004\)
\(=\left(x-3y\right)^2+4\left(x-3y\right)+x^2-10x+4+25+1975\)
\(=\left[\left(x-3y\right)^2+4\left(x-3y\right)+4\right]+\left(x^2-10x+25\right)+1975\)
\(=\left(x-3y+2\right)^2+\left(x-5\right)^2+1975\ge1975\)
Dấu "=" khi \(\begin{cases}\left(x-5\right)^2=0\\\left(x-3y+2\right)^2=0\end{cases}\)\(\Leftrightarrow\begin{cases}x=5\\y=\frac{7}{3}\end{cases}\)
Vậy Min=1975 khi \(\begin{cases}x=5\\y=\frac{7}{3}\end{cases}\)
2)\(x\left(x+1\right)\left(x^2+x-4\right)=\left(x^2+x\right)\left(x^2+x-4\right)\)
Đặt \(t=x^2+x\) ta có:
\(t\left(t-4\right)=t^2-4t+4-4\)
\(=\left(t-2\right)^2-4\ge-4\)
Dấu "=" khi \(t-2=0\Leftrightarrow t=2\Leftrightarrow x^2+x=2\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-2\\x=1\end{array}\right.\)
Vậy Min=-4 khi \(\left[\begin{array}{nghiempt}x=-2\\x=1\end{array}\right.\)
3)\(\left(x^2+5x+5\right)\left[\left(x+2\right)\left(x+3\right)+1\right]\)
\(=\left(x^2+5x+5\right)\left[x^2+5x+6+1\right]\)
Đặt \(t=x^2+5x+5\) ta có:
\(t\left(t+1\right)=t^2+t+\frac{1}{4}-\frac{1}{4}=\left(t+\frac{1}{2}\right)^2-\frac{1}{4}\ge-\frac{1}{4}\)
Dấu "=" khi \(t+\frac{1}{2}=0\Leftrightarrow t=-\frac{1}{2}\Leftrightarrow x^2+5x+5=-\frac{1}{2}\)\(\Leftrightarrow x_{1,2}=\frac{-10\pm\sqrt{12}}{4}\)
Vậy Min=\(-\frac{1}{4}\) khi \(x_{1,2}=\frac{-10\pm\sqrt{12}}{4}\)
4)\(\left(x-1\right)\left(x-3\right)\left(x^2-4x+5\right)\)
\(=\left(x^2-4x+3\right)\left(x^2-4x+5\right)\)
Đặt \(t=x^2-4x+3\) ta có:
\(t\left(t+2\right)=t^2+2t+1-1=\left(t+1\right)^2-1\ge-1\)
Dấu "=" khi \(t+1=0\Leftrightarrow t=-1\Leftrightarrow x^2-4x+3=-1\Leftrightarrow x=2\)
Vậy Min=-1 khi x=2
1.b) \(\left(\left|x\right|-3\right)\left(x^2+4\right)< 0\)
\(\Rightarrow\hept{\begin{cases}\left|x\right|-3\\x^2+4\end{cases}}\) trái dấu
\(TH1:\hept{\begin{cases}\left|x\right|-3< 0\\x^2+4>0\end{cases}}\Leftrightarrow\hept{\begin{cases}\left|x\right|< 3\\x^2>-4\end{cases}}\Leftrightarrow x\in\left\{0;\pm1;\pm2\right\}\)
\(TH1:\hept{\begin{cases}\left|x\right|-3>0\\x^2+4< 0\end{cases}}\Leftrightarrow\hept{\begin{cases}\left|x\right|>3\\x^2< -4\end{cases}}\Leftrightarrow x\in\left\{\varnothing\right\}\)
Vậy \(x\in\left\{0;\pm1;\pm2\right\}\)
a) \(|x+4|=\frac{7}{3}\) \(\Rightarrow x+4=\pm\left(\frac{7}{3}\right)\)
TH1: \(x+4=\frac{7}{3}\)
\(x=\frac{7}{3}-4=-\frac{5}{3}\)
TH2: \(x+4=-\frac{7}{3}\)
\(x=-\frac{7}{3}-4=-\frac{19}{3}\)
1) \(\left|x\right|< 4\Leftrightarrow-4< x< 4\)
2) \(\left|x+21\right|>7\Leftrightarrow\orbr{\begin{cases}x+21>7\\x+21< -7\end{cases}}\Leftrightarrow\orbr{\begin{cases}x>-14\\x< -28\end{cases}}\)
3) \(\left|x-1\right|< 3\Leftrightarrow-3< x-1< 3\Leftrightarrow-2< x< 4\)
4) \(\left|x+1\right|>2\Leftrightarrow\orbr{\begin{cases}x+1>2\\x+1< -2\end{cases}}\Leftrightarrow\orbr{\begin{cases}x>1\\x< -3\end{cases}}\)
\(\left|x+\frac{1}{2}\right|+\left|3-y\right|=0\)
Vì \(\hept{\begin{cases}\left|x+\frac{1}{2}\right|\ge0\\\left|3-y\right|\ge0\end{cases}}\Rightarrow\)\(\left|x+\frac{1}{2}\right|+\left|3-y\right|\ge0\)
Dấu "="\(\Leftrightarrow\hept{\begin{cases}\left|x+\frac{1}{2}\right|=0\\\left|3-y\right|=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=\frac{-1}{2}\\y=3\end{cases}}\)
1) \(\frac{x-1}{3}=\frac{5-x}{7}\Leftrightarrow7.\left(x-1\right)=3.\left(5-x\right)\)
\(\Leftrightarrow7x-7=15-3x\)
\(\Leftrightarrow7x+3x=15+7\)
\(\Leftrightarrow10x=22\)
\(\Leftrightarrow x=\frac{11}{5}\)
2) \(\frac{x-1}{-5}=\frac{-20}{x-1}\)
\(\Leftrightarrow\left(x-1\right)^2=\left(-20\right).\left(-5\right)=100\)
\(\Leftrightarrow100=\orbr{\begin{cases}10^2\\\left(-10\right)^2\end{cases}}\)
Nếu x - 1 = 10 => x = 11
Nếu x - 1 = -10 => x = -9
Vậy ....
3) \(3\sqrt{x-3}+5=\left|-8\right|\)
\(\Leftrightarrow3\sqrt{x-3}+5=8\)
\(\Leftrightarrow3\sqrt{x-3}=3\)
\(\Leftrightarrow\sqrt{x-3}=1\) (ĐK: \(x\ge3\))
\(\Leftrightarrow\left(\sqrt{x-3}\right)^2=1^2\)
\(\Leftrightarrow x-3=1\)
\(\Leftrightarrow x=4\) (nhận)
Vậy x = 4
\(\left|x\right|+3=5\)
\(\Rightarrow\left|x\right|=5-3\)
\(\Rightarrow\left|x\right|=2\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\)
\(\left|x\right|+3=5\)
Vì \(5>3\) nên \(\left|x\right|>0\)
\(x+3=5\)
\(x=5-3\)
\(x=2\)